Comparative Financial Performance Analysis of Banking and Insurance Institutions: Evidence from Bank Rakyat Indonesia and Asuransi Dayin Mitra - Rahmat Riwayat Abadi (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The financial services industry consists of various institutions with different operational models, including banking institutions and non-bank financial institutions such as insurance companies. This study aims to analyze and compare the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk (BRI) and PT Asuransi Dayin Mitra Tbk (ASDM) using financial statement analysis for the 2023–2024 period. The research applies a descriptive comparative method using financial position statements, income statements, and financial ratio analysis. The results indicate that BRI demonstrates strong financial stability supported by a large asset base, strong capital adequacy, and stable profitability derived from interest-based intermediation activities. Meanwhile, ASDM shows significant profit growth driven by underwriting efficiency and investment returns. The analysis also reveals structural differences between banks and insurance companies in asset allocation, revenue sources, leverage structure, and risk exposure. Digital transformation also plays a critical role in improving operational efficiency and expanding financial service ecosystems. Overall, both institutions exhibit strong financial resilience, although their financial strategies and risk management approaches differ according to their respective business models